Recurrent rhabdomyomatous mesenchymal hamartoma: An uncommon benign lesion - Kristen M. Hardy; Cody L. Mullens; Aaron C. Mason (Elsevier, 2021)
Rhabdomyomatous mesenchymal hamartoma (RMH) is an interesting, often unexpected, benign cutaneous lesion that can present in children. Surgical excision is the intervention of choice. This case report describes a case of RMH and is unique in that it is the first instance of a recurrence. A review of the literature is included.